Pengaruh Model Pembelajaran Kooperatif Tipe Time Token Terhadap Keaktifan dan Hasil Belajar Siswa Kelas XI IPS Pada Mata Pelajaran Ekonomi di SMAN 2 Cilacap - Sukendro, Noviani Dwi Wahyudi; Arintoko, Arintoko; Krisnaresanti, Aldila (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This study aimed to analyze the differences and effects of using the time token cooperative learning model on the activity and learning outcomes of class XI IPS students in economics subjects. The research was carried out in the 2022/2023 academic year at SMAN 2 Cilacap. The sampling technique is the purposive sampling technique, in which the determination consists of 70 respondents who are students of class XI IPS 2 and XI IPS 4 and will be tested using an active questionnaire of 19 questions and 15 multiple-choice questions. The results showed that there were differences in the learning activity of class XI IPS students at SMAN 2 Cilacap who were taught using the time token cooperative learning model and the lecture learning model. Second, there are differences in the learning outcomes of class XI IPS students at SMAN 2 Cilacap who are taught using the time token cooperative learning model and the lecture learning model. Third, there is a positive influence of the cooperative learning model of the time token type on the active learning of class XI IPS students in economics at SMAN 2 Cilacap. Fourth, there is a positive influence of the cooperative learning model of the time token type on the learning outcomes of class XI IPS students in economics subjects at SMAN 2 Cilacap.